Morphodynamics and Successional Characteristics of Bowl Blowout in the Late Stage of Coastal Foredune - Shaoyun Zhang; Yuxiang Dong; Wei Tian; Shuyi Fu; Lin Yang (Journal of Marine Science and Engineering)
Coastal foredune blowout is a significant indicator of shoreline retreat, activation of backshore dune fields, and land desertification. Among current research on the terminal phase of coastal foredune blowouts, few studies explain blowouts’ morphological and airflow interaction mechanisms in the late stage through comprehensive field surveys and observations. In this study, the coastal blowout on the foredune at Tannanwan Beach, Pingtan Island, China, is investigated to explore the morphodynamics and evolutionary characteristics of blowout morphology. High-resolution RTK GPS technology and two-dimensional ultrasonic anemometers are utilized to repeatedly measure and observe the morphology of late-stage bowl blowouts. The results revealed that the following: (1) During the entire survey period, the bowl blowout is characterized by deepening erosion of the lateral walls and accretion in the deflation basin, with the maximum erosion depth on the east lateral wall reaching up to 3.99 m and the maximum accumulation height occurring in the front half of the deflation basin. (2) The wind direction and the morphology of the bowl blowout significantly impact the airflow characteristics within the blowout, and the airflow distribution within the blowout further affects the development of the blowout morphology. (3) The bowl blowout is in the late stage of its life cycle.